Specific features of content-based learning and technologies of teaching linguistic competence at academic lyceums and universities - Xo'janazarova Nozima; Badalova Shoxsanam (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article the most important difference lies in the learners and their purposes for learning English. Lyceum and university’s students are usually adults who already have some acquaintance with English and are learning the language in order to communicate a set of professional skills and to perform particular job-related functions. An ESP program is therefore built on an assessment of purposes and needs and the functions for which English is required.